Translator Profile in the Discourse around Translation: Promotion and Reception of the English Translations of the Fiction of Bruno Schulz - Ziemann, Zofia (HERMES - Journal of Language and Communication in Business, 2018)
The paper discusses the role of (perceived) translator profile in the current promotion and reception of three competing English translations of fiction by the modernist Polish-Jewish author Bruno Schulz (1892–1942): Celina Wieniewska’s 1963/1978 canonical version, John Curran Davis’s ca. 2005–2010 online fan retranslation, and Madeline Levine’s retranslation, publicized since 2012 and forthcoming in 2018. Based on a para- and extratextual analysis of the discourse around these versions, combined with archive research into translator history, it explores the ways in which the translator’s profile is used to promote the translation and develop or support opinions about it. Wieniewska’s personal background, difficult to access due to the invisibility of the ‘historical’ translator, has been ignored by readers and critics, even though it would help understand her choice of translation strategy and thus make the recent criticism of her translation more informed. Conversely, in the case of Davis and Levine, not only are the retranslators visible to the extent that they actively promote their work themselves, but also judgments are passed, boundaries drawn and distinctions made based on their profiles rather than their performance: their work has been assessed to a large extent without reference to their actual translation choices. The retranslators’ lives – educational background, affiliation, professional experience – all turn out to play a major role in the critical discourse around their work, replacing the reading or, in the extreme case of Levine’s yet unpublished translation, even the very existence of the translated text.